Harnessing Zero-Tillage: Enhancing Garlic Growth and Yield via Rice Stubble Planting and Mulch Optimization in Far-Western Nepal - Bhatta, Bhawana; Giri, Hom Nath (Agronomy Journal of Nepal, 2025)
Garlic planted in Nepal suffers from low yield due to inadequate soil moisture, delayed planting leading to high temperature exposure, and soil degradation from conventional tillage methods, especially in the areas where it is cultivated as a short winter crop after harvesting the rice. Field research was conducted to evaluate the effect of various tillage and mulching practices in local garlic variety grown after harvesting of rice in Kailali district of Nepal. The field study was conducted at Godawari, Kailali, from November 2021 to April 2022, and evaluated the effects of tillage and mulching on garlic growth and yield using a split-plot design with four replications. The main plot comprised two tillage methods, viz., zero tillage and conventional tillage, whereas the subplot consisted of five mulching practices, i.e., rice straw, rice husk, sawdust, sugarcane trash, and dried leaves. Zero tillage showed significantly higher (p<0.05) plant height (71.1 cm), leaf number (7.51), leaf area (54.79 cm²), clove number (23.46), and yield (17.56 mt/ha). Among mulches, dried leaves and rice straw performed best, with dried leaves yielding 24.83 cloves and 17.57 mt/ha. The highest yield (19.82 mt/ha) came from zero tillage with dried leaves. This combination also improved organic matter, while zero tillage with rice straw improved bulk density and recorded the highest B: C ratio (11.77). Thus, zero tillage with rice straw mulch is recommended for better growth, yield, and profitability in the plains of the far western region of Nepal and areas with similar soil conditions.